Leadership Styles in Sport: A Systematic Review - Fornal, Krystian; Będkowska-Kuśmierek, Natalia; Zaborowska, Sabina; Pawlak, Paulina; Wojcieszuk, Olaf; Starczewski, Łukasz; Babik, Adrianna; Kamińska, Kamila; Będkowska-Kuśmierek, Matylda; Złotnik, Anna (Quality in Sport, 2026)
Background: Leadership is a central determinant of performance, well-being, and organisational effectiveness in sport. Despite a growing body of empirical work, no comprehensive systematic review has synthesised findings across all sport-related leadership contexts, including coaching, physical education, and sport management. Objective: This systematic review aimed to identify, describe, and critically analyse the evidence base on leadership styles in sport published between 2010 and 2025. Methods: A systematic search was conducted in PubMed using a pre-specified Boolean search string in accordance with PRISMA 2020 guidelines [9]. A total of 105 records were retrieved. Following title, abstract, and full-text screening against pre-defined inclusion and exclusion criteria, 43 studies were included in the final synthesis. Results: Transformational leadership was the dominant paradigm, featuring in approximately 65% of included studies. Authentic and servant leadership emerged as important complementary constructs, particularly in relation to athlete well-being and shared leadership. Evidence on destructive leadership was sparse but highlighted significant negative consequences. Leadership research in sport management and governance contexts remained markedly underrepresented. Conclusions: The literature on leadership in sport is heavily skewed towards coach–athlete dyads and transformational leadership theory. Significant gaps remain in the study of leadership within sport organisations and federations, non-Western contexts, and emerging constructs such as paradoxical and ambidextrous leadership. Future research should adopt multi-level and longitudinal designs.